Automatic post-processing for tolerance inspection of digitized parts made by injection moulding. Issue 6 (1st November 2016) - Bici, Michele; Campana, Francesca; Trifirò, Alessio
ABSTRACT: This paper presents the advancements of an automatic segmentation procedure based on the concept of Hierarchical Space Partitioning. It is aimed at tolerance inspection of electromechanical parts produced by injection moulding and acquired by laser scanning. After a general overview of the procedure, its application for recognising cylindrical surfaces is presented and discussed through a specific industrial test case. GRAPHICAL ABSTRACT: